2013
DOI: 10.1134/s0021364013150071
|View full text |Cite
|
Sign up to set email alerts
|

Towards azimuthal anisotropy of direct photons

Abstract: Intensive radiation of magnetic bremsstrahlung type (synchrotron radiation) resulting from the interaction of escaping quarks with the collective confining colour field is discussed as a new possible mechanism of observed direct photon anisotropyThe mighty wealth of experimental data on relativistic heavy ion collisions collected in the different experiments in recent years (even before putting LHC in operation) is reasonably well described (but less well understood) in the framework of approach based on the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 20 publications
2
56
0
Order By: Relevance
“…It was suggested [18] that a considerable additional contribution to the photon production could come due to the boundary bremsstrahlung resulting from the interaction of escaping quarks with the collective confining color field at the surface of the QGP. Obviously, such a mechanism of "magnetic bremsstrahlung-like radiation" (synchrotron radiation in modern terminology) should manifest itself noticeably in the observed anisotropy of direct photons.…”
Section: Photon Radiation At Hadronization Stagementioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested [18] that a considerable additional contribution to the photon production could come due to the boundary bremsstrahlung resulting from the interaction of escaping quarks with the collective confining color field at the surface of the QGP. Obviously, such a mechanism of "magnetic bremsstrahlung-like radiation" (synchrotron radiation in modern terminology) should manifest itself noticeably in the observed anisotropy of direct photons.…”
Section: Photon Radiation At Hadronization Stagementioning
confidence: 99%
“…One of those mechanisms suggests, for example, that a very strong magnetic field created in noncentral heavy ion collisions can increase the photon radiation owing to the conformal anomaly [15] and synchrotron radiation [16,17]. Another mechanism contributing significantly to the observed anisotropy of direct photons refers to a "magnetic bremsstrahlung-like radiation" (synchrotron radiation in modern terminology) of quarks in the collective color field ensuring a confinement [18]. Additional productive sources of electromagnetic radiation when the QCD environment undergoes a confinement have been recently launched in Refs.…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 99%
“…It is pointed out in ref. [34] that the bremsstrahlung of quarks on the surface of QGP, pulled back by the confining force could produce photon radiation in comparable amount to those produced in the plasma phase.…”
Section: I) Strong Electromagnetic (Em) Fieldsmentioning
confidence: 99%
“…There is an ongoing debate in the literature about the contributions of initial and final state asymmetries to the elliptic flow [34][35][36][37]. Emphasizing only a few examples, it is observed that in proton-nucleon collisions the CGC correlations could be directly visible in the measurable particle spectrum.…”
Section: I) Strong Electromagnetic (Em) Fieldsmentioning
confidence: 99%
“…In Ref. [24] it was argued that the observed photon asymmetry may be due to an intensive bremsstrahlung like synchrotron radiation resulting from the interaction of escaping quarks with the collective confining color field at the surface of the QGP. For this mechanism the asymmetry arises due to bigger surface emission from the almond-shaped QGP fireball along the direction of the impact parameter vector (as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%